Analisis Mekanisme End-To-End Security Pada Komunikasi Antara Node Sensor Dengan IoT Middleware - Ahmad Lutfi Bayu Aji; Eko Sakti Pramukantoro; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Internet of things (IoT) is one of the technology of the future that develops rapidly. IoT can use data that has been collected without human help, which then interconnected with each other with the internet. In the previous research, a middleware with an event-driven approach has been developed that can support the interoperability of various devices or sensors. Middleware consists of sensor nodemcu ESP8266 and Raspberry Pi as a broker / server. Sensors communicate using MQTT and CoAP protocols with middleware. Every computer network must have vulnerabilities. One of the attacks on network communication is Man In The Middle (MITM). In the middleware scheme, the security features have not been applied either to data transmission or data validation, so there is a need to overcome the security hole or end-to-end security. In this research we will add TLS and AES-CBC crypto mechanisms to protect data sent from nodemcu sensor to middleware. And get recommendations of security mechanisms that match the specifications of the Nodemcu ESP8266 minimal sensor. As a result, TLS fails to be applied while AES-CBC crypto succeeds and does not affect QoS on data transmission. It is recommended to apply to middleware as end-to-end security.